AN ANALYSIS OF FIGURATIVE LANGUAGE IN DAN BYRD’S SONG LYRICS ENTITLED “BOULEVARD” - Sukmono Bayu Adhi (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2021)
This purpose of this study is trying to analyze the figurative languages ??and its meaning which exist in the lyric of the song “Boulevard”. It is a descriptive qualitative research where data were taken from a songs lyrics website. Data used in this research was a song lyrics entitled